Ù…Ù†Ø´Ø£ Ø§Ù„ØªØ´Ø§Ø¨Ù‡ ÙˆÙ…ØÙ„Ù‡ ÙÙŠ Ø¢ÙŠØ§Øª Ø§Ù„ØµÙØ§Øª (Ø¯Ø±Ø§Ø³Ø© ÙˆØªØÙ„ÙŠÙ„) - Tariq, Hafiz Muhammad (State Institute of Islamic Studies (IAIN) Palu, 2016)
The Holy Quran was revealed to the Holy Prophet Mohammed (Peace be upon him) by Allah Almighty as a final revelation for the whole of mankind. After the time of the Prophet Mohammed, his fellow scholars began writing commentaries on the holy Quran to understand its meaning and its context. The Mufassireen have concluded that the Quran has two types of verses; Muhkam are verses which are clear and have no dispute as to what they actually mean. Mutashabih are verses which have two or more than two options for the readers to infer their meaning and such verses have been open to debate amongst the Islamic scholars. This paper attempts to provide the correct definitions of Muhkam and Mutashabih verses based on the opinions of the classical and modern scholars. Based on the views of the modern and classical scholars, the researcher discusses the different varieties of these two types of verses and removes any objections and contradictions between the two attempting to clear up any such misconceptions. The philosophical reasoning behind the revelation of Mukham and Mutashabih verses is also tackled within this paper to ensure all areas and opinions are covered, giving an unbiased understanding of the subject